A Validated Multiplex Real-Time PCR Assay for the Diagnosis of Infectious Leptospira spp.: A Novel Assay for the Detection and Differentiation of Strains From Both Pathogenic Groups I and II - Pérez, Lester J.; Lanka, Saraswathi; DeShambo, Vanessa J.; Fredrickson, Richard L.; Maddox, Carol W. (Frontiers in Microbiology, 2020)
Leptospirosis is recognized as the most globally widespread reemerging zoonosis and represents a serious threat for both human and animal health. Indeed, leptospirosis is linked to more than 60, 000 human deaths per year and to incalculable economic burden as consequence of medical treatment costs and livestock loss. The increasing number of reports from species of pathogenic Leptospira group II causing disease in both humans and animals constitutes an additional concern to the complex epidemiology of this zoonotic agent. Diagnostic methods based on qPCR have improved the diagnosis of Leptospira in terms of cost, time and reliability, but most of the validated assays fail to detect species from the pathogenic group II. Hence, the current study was aimed to develop and validate a novel multiplex qPCR to enable the specific and selective detection of the whole group of infectious Leptospira, including both pathogenic groups I and II and moreover, selectively discriminate between them. To fit the “fitness of purpose” for the specific detection of infectious Leptospira spp. and further discrimination between both pathogenic groups three target regions on the 16S RNA gene were selected. These targets facilitated a broad and selective spectrum for the detection of all infectious Leptospira with the exclusion of all saprophytic groups and the novel clade of environmental Leptospira. The analytical sensitivity showed by the new assay also enables a wide window of detection for the agent at different stages of infection since the assay was able to efficiently detect at 95% of confidence ~5 leptospires/reaction. From the evaluation of the analytical specificity by in silico and in vitro approaches it was congruently revealed that the primers and probes selected only recognized the specific targets for which the assay was intended. Bayesian latent class analysis of performance of the new assay on 684 clinical samples showed values of diagnostic sensitivity of 99.8% and diagnostic specificity of 100%. Thus, from the evaluation of the analytical and diagnostic parameters the new multiplex qPCR assay is a reliable method for the diagnosis of Leptospira spp.